Point of purchase cigarette promotions before and after the Master Settlement Agreement: exploring retail scanner data. Issue 2 (24th March 2006) - Loomis, B R; Farrelly, M C; Nonnemaker, J M; Mann, N H
Abstract : Background: Evidence indicates that point of purchase (POP) advertising and promotions for cigarettes have increased since the Master Settlement Agreement (MSA). Retail promotions have the potential to offset the effects of cigarette tax and price increases and tobacco control programmes. Objective: To describe the trend in the proportion of cigarette sales that occur as part of a POP promotion before and after the MSA. Design: Scanner data were analysed on cigarette sales from a national sample of grocery stores, reported quarterly from 1994 through 2003. The proportion of total cigarette sales that occurred under any of three different types of POP promotions is presented. Results: The proportion of cigarettes sold under a POP promotion increased notably over the sample period. Large increases in promoted sales are observed following implementation of the MSA and during periods of sustained cigarette excise tax increases. Conclusions: The observed pattern of promoted cigarette sales is suggestive of a positive relationship between retail cigarette promotions, the MSA, and state cigarette tax increases. More research is needed to describe fully the relationship between cigarette promotions and tobacco control policy.